Quality Assessment and storage stability of ube halaya produced in Bohol - Penales, Lara Andriza Dollisen (2013.)
This study was conducted to assess the quality and storage stability of ube halaya produced by DTI-registered processor (Source A) and non-DTI-registered processor (Source B) in the province of Bohol.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Ube halaya